The Use of Growth Factors in Hematopoietic Stem Cell Transplantation - Pusic, I.; DiPersio, J. F. (Current Pharmaceutical Design, 2008)
Mobilized, peripheral blood stem cells (PBSC) are increasingly used for both autologous and allogeneic transplants. Granulocyte- colony-stimulating factor is the most widely used cytokine for mobilization. Several different mechanisms of stem cell mobilization have been proposed including protease-dependent and non-protease- dependent mechanisms. In autologous transplants, the addition of chemotherapy to mobilization can enhance the yield of PBSC collected but with substantial adverse effects, and not necessarily faster engraftment. In allogeneic transplants, the use of mobilized PBSC is associated with faster engraftment and donor chimerism compared to bone marrow. In the majority of studies, the rate of acute graft-versus-host disease (GVHD) has not been shown to be significantly higher with PBSC, but the rate of chronic GVHD appears to be increased. Several different strategies have been proposed for patients and donors who fail initial mobilization, including the use of novel agents. AMD3100 (Plerixafor) works by directly inhibiting the interaction between stromal cell-derived factor-1 and its receptor CXCR4, and mobilizes hematopoietic stem cells within hours. It is being studied alone or in conjunction with growth factors for PBSC mobilization in both autologous and allogeneic settings. Although the use of growth factors after PBSC transplantation results in faster neutrophil engraftment its impact on treatment-related mortality and survival does not appear significant. Here, we review the biology and methods of PBSC mobilization, the effect of growth factors on normal donors and the controversies of growth factor use in the post-transplant setting. We also review the data on novel agents for mobilization of stem cells.
Keywords: AMD3100